Factors affecting feed efficiency, feed intake and daily gain of Awassi lambs - AZIZ, D A; ALKASS, J E; AL-NIDAWI, KA (The Indian Journal of Animal Sciences, 2013)
Daily gain, feed efficiency and feed intake of Awassi lambs during the 0·40 and 41-80 days post- weaning periods were studied. The overall means for daily gain, feed efficiency and feed intake were 160±7.7 and 145±7.0 g/day. 5.480±0.2 and 8.83±0.39 kg feed intake/kg live weight gain. and 827±24 and1053±28 g/day during periood (0-40) and period 2 (41·80) respeclively. Daily gain was affected only by the larning season (1